Can the Skeptic Search for Truth? - Machuca, Diego Emanuel (2021)
Sextus Empiricus associates the Pyrrhonian stance with the activity of inquiry or investigation. In this paper, I propose to examine the skeptic's involvement in that activity because getting an accurate understanding of the nature and purpose of skeptical inquiry will make it possible to delineate some of the distinctive traits of Pyrrhonism as a kind of philosophy. I defend the minority view among specialists according to which (i) Sextus describes both the prospective Pyrrhonist and the full-fledged Pyrrhonist as inquirers into truth, and (ii) the full-fledged Pyrrhonist can, without inconsistency, engage in truth-directed inquiry.